Halal Awareness Among Orang Asli in Sungai Chiong Village, Banding Lake, Perak - Khadijah Othman; Mohammad Aizat Jamaludin; Mohd Anuar Ramli; Mohd Mahyeddin Mohd Salleh (Universiti Sains Islam Malaysia, 2024)
Non-Indexed Publication